2019
DOI: 10.1109/jtehm.2019.2893223
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Developmental Delay in Infants Using Wearable Sensors: Full-Day Leg Movement Statistical Feature Analysis

Abstract: This paper examines how features extracted from full-day data recorded by wearable sensors are able to differentiate between infants with typical development and those with or at risk for developmental delays. Wearable sensors were used to collect full-day (8–13 h) leg movement data from infants with typical development (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…For instance, there may be substantial day-to-day variation in motility, which needs to define a balance between the added information gain vs practical costs of longer recording periods [18]. Preliminary studies have shown, however, that quantitative movement analysis of infants may be possible with accuracy that even allows clinical outcome predictions [1]. Designing an infant medical wearable of this kind is a very multidisciplinary challenge.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there may be substantial day-to-day variation in motility, which needs to define a balance between the added information gain vs practical costs of longer recording periods [18]. Preliminary studies have shown, however, that quantitative movement analysis of infants may be possible with accuracy that even allows clinical outcome predictions [1]. Designing an infant medical wearable of this kind is a very multidisciplinary challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In autism spectrum disorder research, wearable devices have been used to study sleep patterns, stereotyped behaviors, and metabolic disease risk [ 108 , 109 , 110 , 111 , 112 , 113 , 114 ]. Researchers have also used wearables to identify infants with developmental delays and infants with movement disorders associated with cerebral palsy [ 115 , 116 ] and children with ADHD [ 105 ]. While their value for pediatric physical rehabilitation is clear, two special considerations for pediatric wearable device system use are the data collection protocol and the physical design of the device.…”
Section: The Current Situation With Wearable Device Systemsmentioning
confidence: 99%
“…A lack of movement variability was mostly identified in infants who developed delays or disabilities [ 65 , 66 , 67 ] and abnormal GMs were reported in several infants with ASD and NDDs [ 25 , 30 , 68 , 69 ]. Moreover, a previous study measuring kinematic parameters using wearable sensors in 1–8-month-old infants detected different acceleration features between at-risk infants diagnosed with developmental delay or with no diagnosis and infants with typical development [ 70 ].…”
Section: Discussionmentioning
confidence: 99%